Реклама: культурный контекст - Бойцов М.А. Михаил Анатольевич; Горохов В.М. Владимир Маркович; Гринберг Т.Э. Татьяна Эдуардовна; Петрушко М.В. Марина Владимировна (Академия рекламы)
Авт. указаны на 183-й с.